Scientific substantiation of conceptual directions of development of the system of donation and transplantation - Kovtun , Gavrylo; Kaniura , Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2024)
the article is devoted to the substantiation of the conceptual directions for the development of the system of organ donation and transplantation in the regions of Ukraine. The main principles of development are revealed. The basis for the formation of a modern conceptual model of the regional system of organ donation and transplantation has been laid. Materials and methods. To achieve the goals, the work used general scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systemic and structural-functional approaches. Results. Presents the conceptual directions for the development of the regional system of organ donation and transplantation, in the form of a set of principles (from Latin principium - beginning, basis) underlying the development of the system under consideration. The implementation of conceptual directions in modeling a modern conceptual model of the regional system of organ donation and transplantation will provide a model for the formation of strategic management mechanisms, will be the key to the development of regional transplant practice, the provision of affordable highly qualified transplant care to the population, sustainable socio-economic development of the system in the long term. Conclusions. The developed conceptual directions for the development of the system of organ donation and transplantation in the regions of Ukraine are a priority basis for the formation of a modern conceptual model of the regional system of organ donation and transplantation. The system of organ donation and transplantation in the regions of Ukraine is at the beginning of its formation and needs optimization of many organizational processes, which should be carried out systematically, comprehensively and purposefully on the basis of scientifically based principles, legislatively for the benefit of the population of the region.